(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s
(3ChdgG (B:s
(3ShQI eQje cgjYU CeGd CHh YeQh GdgGA dCf CdaGJ CSeGA GdJgLj jBJ hGHf YGeQ s
(3BNQgG (B:s
(3ShQI GdfGS eNJda ajgG hBjgG SJ hdG jNdj SYj ef jJYH ajg Yf GdCLQ hGdKhGH hfNJe cd NGJeI GeQF JhHI jJeMVfjs
(3HChdgG agQSs
(3JHUQI GdYfhGf (B:s
(3JaSjQ GdHjVGhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/109s
(3cTa GdXfhf (B1/186s
Keywords: (3GdJaSjQ hYdhe GdbQBfs